The conflict between Saudi Arabia and Qatar. An attempt to analyze the events of 2017–2021 - Paszyn, Maciej (Koszty współczesnych kryzysów, 2021)
The purpose of this article is to present the events that took place in the Persian Gulf Region in 2017–2021, when the Saudi-Qatar conflict escalated, with the active participation of Iran and, to a lesser extent, Turkey. The study adopted the thesis that the course of the conflict and the behavior of the parties had an impact not only on international relations in the Persian Gulf region. It was a test for the regional organization (GCC) as a forum for mutual understanding between the countries of the region, in the context of Qatar’s persistence in its clash with a powerful neighbor. For Tehran, it was an opportunity to expand its sphere of influence, which, as the events between 2017 and 2021 showed, was partially successful. The method of foreign policy analysis and content analysis was adopted in the study.